Hematic Antegrade Repriming Reduces Emboli on Cardiopulmonary Bypass: A Randomized Controlled Trial. Issue 3 (23rd May 2022) - Blanco-Morillo, Juan; Salmerón Martínez, Diego; Morillo-Cuadrado, Daniel Vicente; Arribas-Leal, Jose María; Puis, Luc; Verdú-Verdú, Alicia; Martínez-Molina, Mercedes; Tormos-Ruiz, Encarnación; Sornichero-Caballero, Angel; Ramírez-Romero, Pablo; Farina, Piero; Cánovas-López, Sergio
Abstract : Particulate and gaseous microemboli (GME) are side effects of cardiac surgery that interfere with postoperative recovery by causing endothelial dysfunction and vascular blockages. GME sources during surgery are multiple, and cardiopulmonary bypass (CPB) is contributory to this embolic load. Hematic antegrade repriming (HAR) is a novel procedure that combines the benefits of repriming techniques with additional measures, by following a standardized procedure to provide a reproducible hemodilution of 300 ml. To clarify the safety of HAR in terms of embolic load delivery, a prospective and controlled study was conducted, by applying Doppler probes to the extracorporeal circuit, to determine the number and volume of GME released during CPB. A sample of 115 patients (n = 115) was considered for assessment. Both groups were managed under strict normothermia, and similar clinical conditions and protocols, receiving the same open and minimized circuit. Significant differences in GME volume delivery (control group [CG] = 0.28 ml vs. HAR = 0.08 ml; p = 0.004) and high embolic volume exposure (>1 ml) were found between the groups (CG = 30.36% vs. HAR = 4.26%; p = 0.001). The application of HAR did not represent an additional embolic risk and provided a four-fold reduction in the embolic volume delivered to the patient (coefficient, 0.24; 95% CI, 0.08–0.72; p = 0.01), which appears to enhance GME clearance of the oxygenator before CPB initiation.